99MTc-Hexamethylpropyleneamine Oxime Imaging for Early Detection of Acute Lung Injury in Rats Exposed to Hyperoxia or Lipopolysaccharide Treatment. Issue 4 (October 2016) - Audi, Said H.; Clough, Anne V.; Haworth, Steven T.; Medhora, Meetha; Ranji, Mahsa; Densmore, John C.; Jacobs, Elizabeth R.
Abstract : ABSTRACT: 99m Tc-Hexamethylpropyleneamine oxime (HMPAO) is a clinical single-photon emission computed tomography biomarker of tissue oxidoreductive state. Our objective was to investigate whether HMPAO lung uptake can serve as a preclinical marker of lung injury in two well-established rat models of human acute lung injury (ALI). Rats were exposed to >95% O2 (hyperoxia) or treated with intratracheal lipopolysaccharide (LPS), with first endpoints obtained 24 h later. HMPAO was administered intravenously before and after treatment with the glutathione-depleting agent diethyl maleate (DEM), scintigraphy images were acquired, and HMPAO lung uptake was quantified from the images. We also measured breathing rates, heart rates, oxygen saturation, bronchoalveolar lavage (BAL) cell counts and protein, lung homogenate glutathione (GSH) content, and pulmonary vascular endothelial filtration coefficient ( K f ). For hyperoxia rats, HMPAO lung uptake increased after 24 h (134%) and 48 h (172%) of exposure. For LPS-treated rats, HMPAO lung uptake increased (188%) 24 h after injury and fell with resolution of injury. DEM reduced HMPAO uptake in hyperoxia and LPS rats by a greater fraction than in normoxia rats. Both hyperoxia exposure (18%) and LPS treatment (26%) increased lung homogenate GSH content, which correlated strongly with HMPAO uptake. Neither of the treatments had an effect on K f at 24 h. LPS-treated rats appeared healthy but exhibited mild tachypnea, BAL, and histological evidence of inflammation, and increased wet and dry lung weights. These results suggest the potential utility of HMPAO as a tool for detecting ALI at a phase likely to exhibit minimal clinical evidence of injury.